2020
DOI: 10.3390/ijerph17103653
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Dating Apps Users: Sociodemographic and Personality Characteristics

Abstract: The development of new technologies, the expansion of the Internet, and the emergence of dating apps (e.g., Tinder, Grindr) in recent years have changed the way to meet and approach potential romantic and/or sexual partners. The recent phenomenon has led to some gaps in the literature on individual differences (sociodemographic variables and personality traits) between users (previous and current users) and non-users of dating apps. Thus, the aim of this study was to analyze the relationship between using dati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 48 publications
5
41
0
1
Order By: Relevance
“…In fact, some authors, such as Weiser et al [ 75 ], collected data that indicated that 60% of the users of these applications were male and 40% were female. Some current studies endorse that being male predicts the use of dating apps [ 23 ], but research has also been published in recent years that has shown no differences in the proportion of male and female users [ 59 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, some authors, such as Weiser et al [ 75 ], collected data that indicated that 60% of the users of these applications were male and 40% were female. Some current studies endorse that being male predicts the use of dating apps [ 23 ], but research has also been published in recent years that has shown no differences in the proportion of male and female users [ 59 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Age. Specific studies have been conducted on people of different ages: adolescents [ 49 ], young people (e.g., [ 21 , 23 , 71 ]), and middle-aged and older people [ 58 ]. The most studied group has been young people between 18 and 30 years old, mainly university students, and some authors have concluded that the age subgroup with a higher prevalence of use of dating apps is between 24 and 30 years of age [ 44 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most apps are free, and users can chat with a large number of people through location-based algorithms using a Global Positioning System (GPS). Interpersonal encounters arranged through apps vary from social networking to finding sexual partners [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%